Socio-economic disparities in Balochistan, Pakistan – A multivariate analysis - Syed Nawaz-ul-Huda; Burke, Farkhunda; Muhammad Azam (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
The causative agents of social and economic inequalities may be multivariate ranging from natural to manmade factors which have varying degrees of susceptibilities to reduction. Efforts of their dilution entail strenuous efforts starting from an understanding of the causative factors, to creating awareness especially among planners whose task is to henceforth channelize resources for its minimization. The present study is an analysis of the multivariate factors responsible for creating both social and economic inequality in Balochistan, considered as one of the most backward provinces of Pakistan. With the help of Multivariate Analysis, a highly advanced econometric method, the causes of disparity in Balochistan have been identified, presented in the form of factors, which have been used as a guideline for suggesting solutions for ameliorating the vicious prevalent condition. The results indicated that a well guided, integrated and sustainable planning prior to total implementation is imperative.